1997
DOI: 10.1016/s0038-1098(97)00317-7
|View full text |Cite
|
Sign up to set email alerts
|

Pressure induced dimerisation of C70

Abstract: Solid CT0 has been subjected simultaneously to high pressures and temperatures (HPHT), with pressures upto 7.5 GPa and temperatures upto 750°C. X-ray diffraction measurements on the recovered samples indicate that the initial h.c.p. solid C70 transforms to a rhombohedral structure which recovers to an f.c.c. structure on annealing. The associated changes in the intra molecular vibrational modes have been probed through infrared (IR) and Raman measurements. The 1R measurements on these HPHT samples show splitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 24 publications
4
20
0
Order By: Relevance
“…Iwasa et al [45] observed a polymerized phase by both solubility studies, X-ray diffraction, and IR/UV/visible spectroscopy after treating either hcp or fcc C 70 for 1 h at 5 GPa at temperatures up to 800 C. As for C 60 , IR spectroscopy showed many new modes and the observed frequencies agreed well with the results of theoretical calculations for dimers. On heating at zero pressure these dimers reverted to pristine C 70 at 300 o C. The final structure after depolymerization was always fcc, irrespectively of the initial lattice structure, indicating that this is the most stable phase of C 70 at 300 o C. Similar results were found by Premila et al [46], using pressures up to 7.5 GPa at temperatures up to 750 K. They identify the structure of the new polymer as rhombohedral, probably consisting of an array of C 70 dimers. Finally, Blank and co-workers [47] carried out studies over a very wide range of pressure and temperature, 4-12.5 GPa and up to 1770 K. In this range they observed three different phases, a rhombohedral phase produced at ''low" temperatures, below 1000 K at 4 GPa or 700 K at 12.5 GPa, a tetragonal, very hard, three-dimensionally polymerized phase at high temperatures above 10 GPa, and a disordered, semi-graphitized, layered structure at very high temperatures at all pressures.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Iwasa et al [45] observed a polymerized phase by both solubility studies, X-ray diffraction, and IR/UV/visible spectroscopy after treating either hcp or fcc C 70 for 1 h at 5 GPa at temperatures up to 800 C. As for C 60 , IR spectroscopy showed many new modes and the observed frequencies agreed well with the results of theoretical calculations for dimers. On heating at zero pressure these dimers reverted to pristine C 70 at 300 o C. The final structure after depolymerization was always fcc, irrespectively of the initial lattice structure, indicating that this is the most stable phase of C 70 at 300 o C. Similar results were found by Premila et al [46], using pressures up to 7.5 GPa at temperatures up to 750 K. They identify the structure of the new polymer as rhombohedral, probably consisting of an array of C 70 dimers. Finally, Blank and co-workers [47] carried out studies over a very wide range of pressure and temperature, 4-12.5 GPa and up to 1770 K. In this range they observed three different phases, a rhombohedral phase produced at ''low" temperatures, below 1000 K at 4 GPa or 700 K at 12.5 GPa, a tetragonal, very hard, three-dimensionally polymerized phase at high temperatures above 10 GPa, and a disordered, semi-graphitized, layered structure at very high temperatures at all pressures.…”
supporting
confidence: 86%
“…More recently, however, high-pressure-high temperature polymerization has indeed been observed [45][46][47]. Iwasa et al [45] observed a polymerized phase by both solubility studies, X-ray diffraction, and IR/UV/visible spectroscopy after treating either hcp or fcc C 70 for 1 h at 5 GPa at temperatures up to 800 C. As for C 60 , IR spectroscopy showed many new modes and the observed frequencies agreed well with the results of theoretical calculations for dimers.…”
mentioning
confidence: 99%
“…The extremely rich behavior of C 60 ‐based network phases just described, suggests the extension of such studies to other fullerenes and in particular to C 70 . However, initial studies have only produced disordered structures and the enthusiasm on C 70 fullerene networks had quickly dropped . The apparent inability of C 70 molecules to form ordered network structures under high pressure, in opposite to C 60 , seemed a natural consequence of their low reactivity and also of constraints on intermolecular bonding imposed by the uniaxial alignment of the low‐symmetric molecules in the solid.…”
Section: Introductionmentioning
confidence: 97%
“…It was shown that the position and the shape of the radial breathing mode (%170 cm ± ±1 ) of SWNT depends on the exciting laser energy which can be explained in terms of a diameter-selective Raman scattering mechanism. We have earlier used Raman spectroscopy to explore the pressure and temperature induced orientational phase transitions in solid C 60 and solid C 70 [10,11], pressure induced amorphisation of solid C 70 [12] and pressure-temperature induced polymeric phases [13,14] of C 60 and C 70 . The main focus of this paper is to discuss our recent results on pressure effects on SWNT bundles probed using Raman spectroscopy upto a maximum pressure of 25.9 GPa in a diamond anvil cell [15].…”
Section: Introductionmentioning
confidence: 99%